2016
DOI: 10.2174/0929867323666160907162002
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Oncogenic Roles of the TRPM7 Chanzyme

Abstract: Transient Receptor Potential Melastatin-related 7 (TRPM7) is a non-selective cation channel fused with a functional kinase domain. Physiologically, TRPM7 channel is involved in magnesium homeostasis, cell survival and gastrulation. The channel part is responsible for calcium, magnesium, and metal trace entries. Cation current through TRPM7 channel is inhibited by both intracellular magnesium and magnesium complexed with nucleotides. In parallel, the kinase is able to phosphorylate cytoskeleton proteins like my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…Here, we show for the first time that TRPM7 channels participate in this neoplastic transformation. TRPM7 is a non-selective cation channel which is overexpressed in numerous cancers, including breast cancer and pancreatic ductal adenocarcinoma (Dhennin-Duthille et al 2011;Gautier et al 2016;Middelbeek et al 2012;Rybarczyk et al 2012;Yee et al 2015). We show that Cd 2+ exposure induces TRPM7 overexpression in both human mammary and pancreatic non-cancer epithelial cells, suggesting that TRPM7 could be used as a biomarker for cell transformation.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Here, we show for the first time that TRPM7 channels participate in this neoplastic transformation. TRPM7 is a non-selective cation channel which is overexpressed in numerous cancers, including breast cancer and pancreatic ductal adenocarcinoma (Dhennin-Duthille et al 2011;Gautier et al 2016;Middelbeek et al 2012;Rybarczyk et al 2012;Yee et al 2015). We show that Cd 2+ exposure induces TRPM7 overexpression in both human mammary and pancreatic non-cancer epithelial cells, suggesting that TRPM7 could be used as a biomarker for cell transformation.…”
Section: Discussionmentioning
confidence: 79%
“…The low selectivity of TRPM7 towards divalent cations may also provide a favorite route for Cd 2+ in epithelial cell leading to cell transformation into a neoplastic phenotype. Numerous studies have shown that TRPM7 is involved in cancer progression (Gautier et al 2016). For instance, TRPM7 is overexpressed in breast cancer and this channel regulates MCF7 cell proliferation (Dhennin-Duthille et al 2011;Guilbert et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the mitochondrial enzyme succinate dehydrogenase has been proposed to be part of a complex giving rise to the mitochondrial ATP‐dependent potassium channel and some ion channels can function as enzyme (chanzymes) (e.g., Ref. ). To our knowledge this is the first case of a mitochondrial enzyme that is shown to function as an ion channel on its own.…”
Section: What Are the Characteristics Of The New Channels In The Omm?mentioning
confidence: 99%
“…Of the eight sub-families in the vertebral TRP family, the melastatin-subfamily (TRPM) possesses unique structural motifs and share common architectural features [4]. Growing evidence has shown that the TRPM7 member plays crucial roles in cellular processes, embryonic development, and human diseases, particularly cancer [5,6,7,8]. Accumulating data suggest the potential value of TRPM7 as a molecular biomarker and therapeutic target in human malignancies [5,8,9].…”
Section: Introductionmentioning
confidence: 99%